Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Jalan pada Rumah Sakit Ibu dan Anak An Nisa Kota Jambi - Abdul Rahman (Universitas Batanghari Jambi, 2021)
Health is a primary need for everyone. To meet these needs, adequate health services are needed, especially for people who experience health problems. One of them can be obtained through the hospital. Hospital as a business engaged in the field of services must provide quality services, so as to provide satisfaction to patients. This study aims to find out the effect of quality of care on outpatient satisfaction at An Nisa Kota Jambi Mother and Child Hospital. This type of research is descriptively quantitative. The population in this study was outpatients at An Nisa Kota Jambi Mother and Child Hospital in 2020 which amounted to 12,622 people. The sample numbered 100 people. Sampling is done by stratified random sampling. Scale of measurement using the likert scale. The instrument used is a questionnaire. Data analysis is done using a simple linear regression formula. An Nisa hospital was established in 2017, and focuses on maternal and child services. This hospital has carried out excellent health service procedures with operational standards in accordance with government regulations, especially regulations in the field of health. The hospital is led by a director named dr. Hj. Nadiah, Sp.OG. To date, the hospital has had sixteen polyclinics. The results showed that the variable score of service quality got an average score of 429, while patient satisfaction earned an average score of 418. Regression analysis results obtained equation Y = -0.218 + 1.084X. Correlation coefficient of 0.817. Thitung value of 14,043 and significance of 0.000. Based on the results of the study, it can be concluded that the quality of service at An Nisa Kota Jambi Mother and Child Hospital falls into the category of very good. Patient satisfaction falls into the category of satisfaction. The quality of service has an effect on outpatient satisfaction by 66.8%. The quality of service has a positive and significant effect on the satisfaction of outpatients at An Nisa Ibu and Anak Hospital in Jambi City.